2020
DOI: 10.21037/atm-20-3315
|View full text |Cite
|
Sign up to set email alerts
|

Application of telemedicine during the coronavirus disease epidemics: a rapid review and meta-analysis

Abstract: Background: As COVID-19 has become a global pandemic, early prevention and control of the epidemic is extremely important. Telemedicine, which includes medical advice given over telephone, Internet, mobile phone applications or other similar ways, may be an efficient way to reduce transmission and pressure on medical institutions.Methods: We searched MEDLINE, Web of Science, Embase, Cochrane, CBM, CNKI and Wanfang databases for literature on the use of telemedicine for COVID-19, SARS and MERS from their incept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“… 61 Common uses of telemedicine include video or phone consultations, allowing individuals with chronic conditions to self-monitor symptoms and send this information to their clinicians, mobile apps, and platforms. 55 , 62 For chronic heart failure patients, virtual care has enabled effective routine monitoring (eg, heart rhythm, blood pressure, O 2 saturation) associated with better compliance with treatment rates (51% vs 35%) and follow-up rates than in-person care during COVID-19. 63 Among patients with chronic respiratory conditions such as asthma or COPD, remote care has been effective for self-management education (eg, inhaler device training, breathing techniques, recognizing symptoms, forming or complying with action plans, etc.…”
Section: Healthcare Characteristics and Utilization By Individuals Wimentioning
confidence: 99%
“… 61 Common uses of telemedicine include video or phone consultations, allowing individuals with chronic conditions to self-monitor symptoms and send this information to their clinicians, mobile apps, and platforms. 55 , 62 For chronic heart failure patients, virtual care has enabled effective routine monitoring (eg, heart rhythm, blood pressure, O 2 saturation) associated with better compliance with treatment rates (51% vs 35%) and follow-up rates than in-person care during COVID-19. 63 Among patients with chronic respiratory conditions such as asthma or COPD, remote care has been effective for self-management education (eg, inhaler device training, breathing techniques, recognizing symptoms, forming or complying with action plans, etc.…”
Section: Healthcare Characteristics and Utilization By Individuals Wimentioning
confidence: 99%
“…During the SARS epidemic of 2002, several provinces in China and Taiwan maintained hotline consultation services that provided medical counseling, including instructions on infection prevention and tracking of suspected cases. [ 16 ]. The main disadvantage of these services was the reallocation of health professionals to telescreening activities, reducing the number of regular medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Given that participation and data sharing are nonbinding, the privacy-first approach could consistently generate skepticism but ideally will enable the implementation to mitigate current and subsequent cyclical pandemics [ 41 ]. Coupled with the efforts from a variety of responders, the rate of participation and delays in data sharing are expected to improve over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rapid adoption of compulsory digital health measures without public consensus and discussions could provoke debates due to the fundamental heterogeneity in the attitudes regarding how digital health should function and, crucially, who should have access to the generated data [ 38 - 42 , 44 , 45 ]. Residents’ perception of privacy and trust in public authorities can vary from culture to culture, which can impact the captured definition of individual privacy preservation [ 39 - 41 ]. A survey conducted in five other countries (ie, France, Germany, Italy, the United Kingdom, and the United States) found that people in settings with stronger public privacy and security concerns are relatively less supportive of app-based contact tracing, and individuals with less trust in public authorities are also less supportive [ 46 , 47 ].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%